Distinct Intraseasonal Oscillation Modes Over the Tropical Indo‐Pacific Oceans - Yiran Li; Haibo Hu; Fei Liu; Matthew Patterson; Xiu‐Qun Yang; Kecheng Lu; Kefeng Mao; Ziyi Wang; Rongrong Wang (Geophysical Research Letters)
Abstract In boreal winter, the Madden‐Julian Oscillation (MJO) is the dominant mode of tropical intraseasonal oscillation (ISO), which bridges weather and climate. In addition to the dominant eastward propagating MJO mode, this study identifies the existence of the westward propagating and stationary oscillating ISO modes according to the spatio‐temporal evolution of large‐scale precipitation. At the pentad timescale, each ISO mode tends to suppress the occurrence of the other two. The diagnostic of column‐integrated moist static energy (MSE) tendency anomalies reveals the dominant contribution from horizontal MSE advection to each ISO mode. Synthesis results indicate that vertical zonal wind shear anomalies exhibit opposite distributions between the propagating and stationary oscillating ISO events over the tropical Indo‐Pacific Oceans. Subsequent simulations prove that the easterly (westerly) wind shear anomalies could suppress the eastward (westward) propagating convection of the ISO, thus favoring a stationary oscillating ISO.